Endoscopic-assisted transorbital surgery: Where do we stand on the scott’s parabola? personal considerations after a 10-year experience - Dallan, Iacopo; Cristofani-Mencacci, Lodovica; Fiacchini, Giacomo; Turri-Zanoni, Mario; van Furth, Wouter; de Notaris, Matteo; Picariello, Miriana; Alexandre, Enrico; Georgalas, Christos; Bruschini, Luca (Frontiers in Oncology, 2022)
Transorbital approaches are genuinely versatile surgical routes which show interesting potentials in skull base surgery. Given their “new” trajectory, they can overcome some limits of traditional routes and add valuable opportunities in selected patients. Indications are constantly expanding, and currently include selected intraorbital, skull base and even intra-axial lesions, both benign and malignant. Given their relatively recent development and thus unfamiliarity among the skull base community, achieving adequate proficiency needs not only a personalized training and knowledge but also, above all, an adequate case volume and a dedicated setting. Current, but mostly future, applications should be selected by genetic, omics and biological features and applied in the context of a truly multidisciplinary environment.